PENGGUNAAN BEBERAPA JENIS PUPUK DAUN DAN JENIS BAHAN WADAH PADA FASE PEMBUNGAAN Phalaenopsis sp. - Astutik Astutik; Astri Sumiati; I Made Indra Agastya; Sutoyo Sutoyo (Universitas Tribhuwana Tunggadewi, 2022)
The research aimed to determine the type of foliar fertilizer and container for the flowering phase of lunar orchids. The study was conducted from November 2021 to February 2022, using a completely randomized design with two treatment factors and eight treatment combinations repeated three times. The combinations of these treatments are (a) Type of plastic container and Gandasil B leaf fertilizer 1 g/l (P1G1); (b) Type of plastic container and Gandasil B leaf fertilizer 2 g/l (P1G2); (c) Type of plastic container and Vanda's leaf fertilizer 1 g/l (P1G3); (d) Type of plastic container and Vanda's leaf fertilizer 2 g/l (P1G4); (e) Type of container for coconut coir and Gandasil B leaf fertilizer 1 g/l (P2G1); (f) Type of container for coconut coir and Gandasil B leaf fertilizer 2 g/l (P2G2); (g) Type of container for coconut coir and Vanda's leaf fertilizer 1 g/l (P2G3) and (h) Type of container for coconut coir and Vanda's leaf fertilizer 1 g/l (P2G4). Observations included parameters: number of leaves, leaf width, leaf length, when the stalk appears, stalk length, and number of flowers. The results showed that there is an interaction between the type of container and foliar fertilizer in supporting the flowering of Phalaenopsis sp. This type of coir container with Gardasil B fertilization of 2 g/l can produce flower stalks about seven months after transplanting and at the age of 8 months, the flower stalk length reaches 12 cm with the number of flower buds 2 – 3 buds per plant.